1999
DOI: 10.1038/sj.cgt.7700052
|View full text |Cite
|
Sign up to set email alerts
|

Induced immunity by expression of interleukin-2 or GM-CSF gene in murine neuroblastoma cells can generate antitumor response to established tumors

Abstract: We examined whether antitumor immunity could be generated by the inoculation of cytokine-producing murine neuroblastoma cells (C1300), and whether the immunity might be effective for the established tumors of wild-type (wt) cells. For that purpose, we transduced low immunogenic C1300 cells with interleukin-2 (IL-2), GM-CSF, or IL-4 genes. A loss of tumorigenicity in syngeneic mice was observed using IL-2-and GM-CSF-but not IL-4-producing C1300 cells, although their in vitro growth rates were not affected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Irradiated parental tumors, when injected into immunocompetent animals, can sometimes generate systemic immunity, and cytokine secretion from the tumors efficiently increases the vaccine effect. This immunization procedure is effective even to established tumors and can decrease the number of preexisting metastatic foci [145,148]. Expression of GM-CSF gene in tumor cells do not generally induce systemic immunity, when the tumor cells are inoculated.…”
Section: Tumor Vaccine Using Cytokine-producing Cellsmentioning
confidence: 99%
“…Irradiated parental tumors, when injected into immunocompetent animals, can sometimes generate systemic immunity, and cytokine secretion from the tumors efficiently increases the vaccine effect. This immunization procedure is effective even to established tumors and can decrease the number of preexisting metastatic foci [145,148]. Expression of GM-CSF gene in tumor cells do not generally induce systemic immunity, when the tumor cells are inoculated.…”
Section: Tumor Vaccine Using Cytokine-producing Cellsmentioning
confidence: 99%
“…This strategy was also applied to neuroblastoma in preclinical animal models and initial clinical trials. Thus, ex vivo gene transfer of IL-2 in a murine neuroblastoma model decreased tumorigenicity and enhanced systemic immunity followed by the regression of preestablished hepatic metastases (3). IL-2 was established as a T cell growth factor and has remained the focus of considerable attention as an agent for cancer immunotherapy because of its stimulatory effect on a broad range of immune cell types, including both T and B cells, monocytes, macrophages, and natural killer (NK) cells.…”
mentioning
confidence: 99%
“…As IL‐22 induces the expression of acute‐phase proteins in liver [10], we examined whether liver metastasis could be modulated by IL‐22 secreted from tumours. Intravenous injection of C1300 cells caused liver metastasis and consequently the ratio of liver to body weight increased [16]. We inoculated parent or C1300/IL‐22 cells into syngeneic mice through tail vein and found that the number of liver metastasis and the weight ratio were not different between parent cell‐ and C1300/IL‐22 cell‐injected groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the liver metastasis experiment, A/J mice were intravenously injected with C1300 or transduced cells (5 × 10 5 ) from tail vein and then the number of metastatic foci and the ratio of liver weight to whole body weight were examined on day 21. In this metastasis experiment, few metastatic foci were found in organs other than liver and bone marrow [16].…”
mentioning
confidence: 99%